2015
DOI: 10.1016/j.ijpddr.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in prevalence of Plasmodium falciparum molecular markers selected for by artemether–lumefantrine treatment in pre-ACT and post-ACT parasites in western Kenya

Abstract: Artemether–lumefantrine (AL) became the first-line treatment for uncomplicated malaria in Kenya in 2006. Studies have shown AL selects for SNPs in pfcrt and pfmdr1 genes in recurring parasites compared to the baseline infections. The genotypes associated with AL selection are K76 in pfcrt and N86, 184F and D1246 in pfmdr1. To assess the temporal change of these genotypes in western Kenya, 47 parasite isolates collected before (pre-ACT; 1995–2003) and 745 after (post-ACT; 2008–2014) introduction of AL were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 53 publications
17
47
1
Order By: Relevance
“…Previous studies demonstrated that LU may select for CQ-sensitive alleles such as the Pfmdr-1 N86 and Pfcrt K76 alleles, and these alleles have been associated with AL treatment failure (46,47). Our study and recent studies in western Kenya show a significant increase in the prevalence of the WT allele at codon K76 of Pfcrt and an upward trend in the prevalence of WT alleles in Pfmdr-1 codons N86 and N1246 in parasites collected after the introduction of ACT in Kenya (31). Therefore, the use of AL as the first line of malaria treatment in Kenya may be contributing to the selection of these wild-type alleles.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous studies demonstrated that LU may select for CQ-sensitive alleles such as the Pfmdr-1 N86 and Pfcrt K76 alleles, and these alleles have been associated with AL treatment failure (46,47). Our study and recent studies in western Kenya show a significant increase in the prevalence of the WT allele at codon K76 of Pfcrt and an upward trend in the prevalence of WT alleles in Pfmdr-1 codons N86 and N1246 in parasites collected after the introduction of ACT in Kenya (31). Therefore, the use of AL as the first line of malaria treatment in Kenya may be contributing to the selection of these wild-type alleles.…”
Section: Discussionsupporting
confidence: 64%
“…For example, 10 years after the discontinuation of CQ for malaria treatment in Malawi, several studies demonstrated the return of CQ-sensitive parasites and an increase in the prevalence of parasites harboring the wild-type (WT) Pfcrt K76 codon (22,23). Similar trends were later reported from studies conducted in other parts of Malawi (24,25), Tanzania (26,27), and Kenya (28)(29)(30)(31), raising the possibility of the selected reintroduction of CQ for malaria treatment. In contrast, countries that delayed the withdrawal of CQ for malaria treatment demonstrated no significant decreases in the prevalence of CQ resistance parasites (reviewed in reference 32), implying that drug pressure plays a major role in the maintenance of drug-resistant parasites in a population.…”
mentioning
confidence: 54%
“…Variations in the IC 50 of antimalarial drugs between parasite lines expressing wild type pfmdr1-Y184 or mutant 184F were shown to be closely linked to either of pfmdr1 N86 or 86Y alleles and not the 184F allele [53]. However, several epidemiological studies on the prevalence of pfmdr1 Y184F polymorphisms have shown that the Y184 allele is predominantly con ned to East and Central Africa while the mutant 184F allele predominates in West Africa [1,32,36,48]. Indeed, reports of the high occurrence of the mutant pfmdr1 184F in West Africa were corroborated by the present ndings in which we show that the prevalence of pfmdr1 184F was high in all the states, and especially in Kano, and that its prevalence is higher in North-West compared to North-East Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published primers for Pfcrt K76T and Pfmdr1 SNPs for allele polymorphisms were used for PCR and sequencing analyses. Concentration of PCR reactants, purifying of the successfully amplified targets for eventual sequencing or PCR-based single-base extension assays followed by contig assembly ad analysis were done as previously described [12][13][14]. Polymorphisms in the Pfap2mu and Pfubp1genes were determined by direct sequencing of 3 fragments encompassing codons 1-174, 121-399 and 377-621 in the former and codons 1463-1563 for the later as described by Henriques et al [2].…”
Section: Detection Of Genetic Polymorphisms and Copy Number Estimationmentioning
confidence: 99%